2020
DOI: 10.1117/1.jei.29.2.023011
|View full text |Cite
|
Sign up to set email alerts
|

DPSA: dense pixelwise spatial attention network for hatching egg fertility detection

Abstract: © 2020 SPIE and IS & T. Deep convolutional neural networks show a good prospect in the fertility detection and classification of specific pathogen-free hatching egg embryos in the production of avian influenza vaccine, and our previous work has mainly investigated three factors of networks to push performance: depth, width, and cardinality. However, an important problem that feeble embryos with weak blood vessels interfering with the classification of resilient fertile ones remains. Inspired by fine-grained cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…These results showed that the PLS algorithm used can discriminate both brown and white fertile eggs from non-fertile eggs prior to incubation, using any of the thresholds identified. This is a huge contribution when compared to earlier studies that have not achieved such accuracies prior to incubation, with some studies reporting only the overall accuracy metric, which cannot capture the prevalent class overfitting problem in a rare-class data scenario [ 17 , 18 , 19 , 20 , 33 ]. Emerging studies should deliberately consider handling the imbalanced data occurrence and feasibility of building a multi-purpose singular model to handle both brown and white eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that the PLS algorithm used can discriminate both brown and white fertile eggs from non-fertile eggs prior to incubation, using any of the thresholds identified. This is a huge contribution when compared to earlier studies that have not achieved such accuracies prior to incubation, with some studies reporting only the overall accuracy metric, which cannot capture the prevalent class overfitting problem in a rare-class data scenario [ 17 , 18 , 19 , 20 , 33 ]. Emerging studies should deliberately consider handling the imbalanced data occurrence and feasibility of building a multi-purpose singular model to handle both brown and white eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unsupervised classification is always the starting point in any discrimination problem and should be necessarily followed by supervised classification [ 16 ], towards an industrial adoptability consideration. More recent works [ 17 , 18 , 19 , 20 ] have attempted approaches, including the state-of-the-art deep learning architecture, for studying chicken egg fertility. Such works, however, were not successful in fertility detection prior to incubation (day 0 of incubation).…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that the PLS algorithm used can discriminate both brown and white fertile eggs from non-fertile eggs prior to incubation, using any of the thresholds identified. This is a huge contribution when compared to earlier studies that have not achieved such accuracies prior to incubation, with some studies reporting only the overall accuracy metric, which cannot capture the prevalent class overfitting problem in a rareclass data scenario [17][18][19][20]33]. Emerging studies should deliberately consider handling the imbalanced data occurrence and feasibility of building a multi-purpose singular model to handle both brown and white eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unsupervised classification is always the starting point in any discrimination problem and should be necessarily followed by supervised classification [16], towards an industrial adoptability consideration. More recent works [17][18][19][20] have attempted approaches, including the state-of-the-art deep learning architecture, for studying chicken egg fertility. Such works, however, were not successful in fertility detection prior to incubation (day 0 of incubation).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it was not stated clearly how the different classes of fertile, infertile, and dead embryo eggs was determined. In the same vein, a follow up study to [ 27 ] by [ 28 ] adopted a dense pixelwise spatial attention (DPSA) network for hatching egg fertility classification. The same methodology as in [ 27 ] was followed and so the questions regarding image data source and classes determination remain unanswered.…”
Section: Assessment Of Chicken Egg Fertilitymentioning
confidence: 99%